Conceptual Foundations of the Ideographic Dictionaries of the Ural Semantic School - Babenko, Liudmila G.; Dudorova, Maria V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2024)
The purpose of the article is to examine the ideographic dictionaries created by the lexicographers of the Ural Semantic School from the dynamic aspect, according to which the Ural ideographic lexicography was formed as an independent direction. In total, the group has published 26 ideographic dictionaries of different semantic and grammatical nature of words: verbs, nouns, adjectives, synonyms of the Russian language and Russian speech, synonymic-antonymic complexes, Russian verb sentences, Russian key concepts. The methodological basis of such dictionaries were the basic provisions of the main scholarly paradigms of the late twentieth and early twenty-first centuries: structural-semantic, functional-semantic, denotative-ideographic, cognitive-discursive. In turn, a new type of active ideographic dictionaries contributed to the formation of a system of basic theoretical positions that formed the conceptual lexicographic base of ideographic dictionaries. The universal theoretical foundations of linguistic construction represent the following fundamental principles: consistency, hierarchy, invariance/variability, the presence of standard semantics, representativeness of identifiers, etc., the implementation of which is modified and corrected in the structure of various ideographic dictionaries and supplemented with new relevant lexicographic parameters of their construction, which determines the conceptual uniqueness of each individual dictionary. The peculiarities of such dictionaries and their ideographic sets are determined by the semantic-grammatical and linguo-cognitive nature of the units that make up their composition and the specifics of their constituent sets of units: lexical-semantic, functional-semantic and functional-syntactic, cognitive-discursive. As a result of the study, the authors identify the main types of lexical sets in the composition of ideographic dictionaries of different types.